Uso da ficha técnica de preparação como ferramenta de qualidade na produção de refeições coletivas - SOARES, Elaine Cristina Silva (2023)
Introduction: The Technical Preparation Form (FTP) is a managerial tool for operational support used in Meal Production Units (UPR) which has several purposes, including the standardization of the production process. Objective: To analyze the vegetarian FTPs served in a University Restaurant of a Federal Teaching Institution in BelémPA: regarding the items that make up the form, the nutritional composition and the culinary indicators. Methodology: This is a crosssectional study, with documentary analysis of 19 (nineteen) FTPs of the main course options served to the university community. The study period was from March 2020 to February 2021. The following were carried out: a) Evaluation of the technical data sheets used in the unit, listing the information that appears and the information that needs to be included in this tool. b) analysis / nutritional adequacy of vegetarian preparations based on the consultation of Food Composition Tables and nutritional information contained on food labels. The caloric value, the percentage of macronutrients (proteins, carbohydrates and lipids) were evaluated. c) The use of culinary indicators: portion and unit cost of preparations. The data obtained were compared with WHO recommendations (Dietary Reference Intakes (DRIs) for adult men and women and with Interministerial Ordinance No. 66/2006. Results: The analyzed vegetarian FTP's are not in compliance with all parameters provided for in literature, as they did not provide important and fundamental data for the control of purchases and production.With respect to culinary indicators the average portion / per capita (kg) was 0.220 ± 0.04 and the unit cost was R $ 1.43 ± 0.58. Regarding the percentage distribution of the Total Energy Value (VET) of the preparations (kcal) was 252.61 ± 69.52,% of NDPCal, 7.06 ± 4.23 and the fractions of the macronutrients: proteins ( 14.32 ± 3.26), carbohydrates (57.53 ± 13.82) and lipids (28.15 ± 12.47), respectively. Conclusion: FTP is considered a widely used resource in UPRs, since it has the purpose of guaranteeing the reproduction of the preparation with quality, adequate nutritional value, regardless of who has prepared it plowed, it serves as an effective tool of work in all stages of the production process, helps in promoting a balanced and healthy diet and influences positively on customer satisfaction.